Microbial profile and susceptibility patterns of diabetic foot ulcers in patients treated at a tertiary hospital - Motsepe, Tshepang Arthur; Machowski, A; Shikwambane-Ntlemo, G; Mabitsela, M; Mthelebofu, B Mthelebofu; Maritz, SM (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2023)
The increase in the number of patients with diabetes mellitus has been associated with a rise in its complications, including a diabetic foot. The study aimed to determine types of microorganisms present in diabetic foot ulcers in [location deleted...], and to analyse their susceptibility patterns to commonly used antibacterial drugs. In this retrospective cross-sectional study, analysis of specimens from wounds of diabetic patients seen [Affiliated institutions deleted…] was carried out. Stored data for a five-year period starting from 01 July 2017 to 30 June 2022 was used. The study consisted of 97 patients. There were 53 (54.6%) males and 44 (45.4%) females between the ages of 15 and 83 years. From the specimens, 150 bacteria were isolated with Gram positive isolates being 80 (53%) and Gram negative isolates 70 (47%). Staphylococcus aureus was the predominant organism, and displayed an overall resistance of 80% against penicillins and with 19% of its isolates being methicillin resistant. Considering the above, a question remains about which empiric drug to use for resistant Gram positive organisms, as Gram positive isolates form most of the organisms cultured in diabetic foot ulcers in our setting. The results of the study are crucial in guiding clinicians on the best choice of empiric antibiotics in our setting. Until now, such information in literature from Ga-Rankuwa does not exist.